Multi-Omics Approach to Dissect the Mechanisms of Rexinoid Signaling in Myoblast Differentiation - Khilji, Saadia; Li, Yuan; Chen, Jihong; Li, Qiao (Frontiers in Pharmacology, 2021)
Stem cells represent a key resource in regenerative medicine, however, there is a critical need for pharmacological modulators to promote efficient conversion of stem cells into a myogenic lineage. We have previously shown that bexarotene, an agonist of retinoid X receptor (RXR) approved for caner therapy, promotes the specification and differentiation of skeletal muscle progenitors. To decipher the molecular regulation of rexinoid signaling in myogenic differentiation, we have integrated RNA-seq transcription profiles with ChIP-seq of H4K8, H3K9, H3K18, H3K27 acetylation, and H3K27 methylation in addition to that of histone acetyl-transferase p300 in rexinoid-promoted myoblast differentiation. Here, we provide details regarding data collection, validation and omics integration analyses to offer strategies for future data application and replication. Our analyses also reveal molecular pathways underlying different patterns of gene expression and p300-associated histone acetylation at distinct chromatin states in rexinoid-enhanced myoblast differentiation. These datasets can be repurposed for future studies to examine the relationship between signaling molecules, chromatin modifiers and histone acetylation in myogenic regulation, providing a framework for discovery and functional characterization of muscle-specific loci.